Роль основних стандартних патентів у розбудові 5G: вплив регуляторної політики ЄС на електронний бізнес - Єфремова, К. В.; Yefremova, K. V.; Шматков, Д. І.; Shmatkov, D. I. (Право.ua. - 2024. - № 3. - С. 315-321, 2024)
У статті розглянуто вплив регуляторної політики ЄС на електронний бізнес шляхом ліцензування основних стандартних патентів (SEP) у сфері ІКТ, зокрема 5G. Підкреслено необхідність уникнення антимонопольних зловживань, таких як «прихований патент». Проаналізовано пропозицію Єврокомісії щодо вдосконалення ліцензійного регулювання SEP, що передбачає реєстрацію патентів в EUIPO, визначення сукупного роялті, встановлення часових рамок для позасудового механізму вирішення спорів, створення патентних пулів для спрощення процесу ліцензування та нові можливості для бізнесу в цифровій економіці. Зроблено висновки щодо постійно зростаючої кількості 5G SEP, які не мають незалежних оцінок необхідності заявлених патентів для стандарту 5G, що може призвести до додаткових ліцензійних витрат (складання роялті), які частково перекладуться на кінцевих користувачів.

The article is devoted to the issues of legal regulation of licensing of standard essential patents (SEPs) in the field of ICT. The purpose of the study is to define the role of standard essential patents and their impact on e-business and industries using the Internet of Things (IoT), using the example of 5G technology standards, and to analyse the regulatory impact of the European Commission and the EU Standard Essential Patents Board on the licensing of essential ssential patents (SEPs). The authors described potential challenges for the EU in the field of patent regulation. FRAND-based policies have so far been the only way to manage the tensions between patent holders, standards bodies and end users. Using the FRAND (fair, reasonable and nondiscriminatory access) concept ensures a balance between the rights of patent holders and users, but the implementation of these rules requires coherence of interests and effective control mechanisms to avoid abuses such as ‘hidden patents’. The researchers analysed the European Commission’s proposal to improve SEP licensing regulation, which includes registration of patents with the EUIPO, determination of aggregate royalties, setting time limits for outof-court dispute resolution, creation of patent pools to simplify the licensing process and new business opportunities in the digital economy. Changes to SEP regulation create new rules aimed at balancing the interests of patent holders and technology users, which are key to ensuring competitiveness, access to innovation and preventing abuse of dominance. Regulatory control is being increased and interoperability is being promoted. The authors expressed support for the decision to create patent pools. Patent pools combine different SEPs from different owners into a single package that licensees can purchase under a single contract. This significantly reduces administrative costs, simplifies the licensing process, and allows companies to get access to all the patents they need to implement standards such as 5G faster. It also reduces the risk of patent disputes, as the rights to use the technology are agreed upon in one pool. Conclusions are drawn regarding the evergrowing number of 5G SEPs that do not have independent assessments of the need for the claimed patents for the 5G standard, which may lead to additional licensing costs (royalty compounding), which will be partially passed on to end users.

Определена роль основных стандартных патентов и их влияние на электронный бизнес и отрасли, использующие Интернет вещей (IoT), на примере стандартов технологии 5G.
The role of standard essential patents in the development of 5G: the impact of EU regulatory policy on e-businessr
Keywords: електронний бізнес; право інтелектуальної власності; основні стандартні патенти; SEP; стандарт 5G; FRAND; патентний пул; e-business; intellectual property law; standard essential patents; 5G standard; patent pool; электронный бизнес; право интеллектуальной собственности; основные стандартные патенты; патентный пул